2015
DOI: 10.1111/hex.12385
|View full text |Cite
|
Sign up to set email alerts
|

I just don't want to get bullied anymore, then I can lead a normal life’; Insights into life as an obese adolescent and their views on obesity treatment

Abstract: BackgroundAdolescent obesity is a complex condition involving social, emotional, behavioural and cultural issues.DesignOne‐to‐one interviews and small focus groups with overweight and obese young people were conducted. Qualitative research is an appropriate method to explore the complexity of this issue.Setting and participantsOverweight and obese adolescent's attending a community weight management intervention in South Yorkshire.Main variables studiedInterviews aimed to explore the experiences of obese adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(87 citation statements)
references
References 47 publications
2
85
0
Order By: Relevance
“…Normality, from the point of view of an adolescent in these studies, suggested having a boyfriend and the ability to socialize and play with friends . As well as seeing weight loss as the key to social desirability, some adolescents felt that losing weight would reduce the bullying they received, which would lead to a normal and happy life .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Normality, from the point of view of an adolescent in these studies, suggested having a boyfriend and the ability to socialize and play with friends . As well as seeing weight loss as the key to social desirability, some adolescents felt that losing weight would reduce the bullying they received, which would lead to a normal and happy life .…”
Section: Resultsmentioning
confidence: 95%
“…Many adolescents viewed being a healthy weight as normal and held this as the key to being accepted socially . Normality, from the point of view of an adolescent in these studies, suggested having a boyfriend and the ability to socialize and play with friends .…”
Section: Resultsmentioning
confidence: 97%
“…Emotional eating was considered a barrier to adopting healthy food habits by adolescents with obesity in a number of studies , some of whom engaged in disordered eating behaviours when faced with upsetting or emotional circumstances . In particular, adolescents reported that anxiety , loneliness , sadness and being upset influenced the quantity and/or quality of the food that they consumed.
I think one of the reasons why I probably, I comfort eat a lot and there's like stuff going on, well used to be stuff going on at home which kind of like used to upset me a lot and I used to comfort eat.
…”
Section: Barriers: Nutritionmentioning
confidence: 99%
“…Rankin et al , ; Kelsey et al , ). In addition, various studies conclude that obesity stigma and bullying can harm emotional and physical well‐being of obese adolescents (Puhl and King, ; Rankin et al , ; Reece, Bissell and Copeland, ).…”
Section: Introductionmentioning
confidence: 99%